2020
DOI: 10.2741/s541
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of green tea on age related diseases

Abstract: Green tea (Camellia sinensis, Theaceace), has been extensively studied for its putative effects in prevention of age related diseases. Here, we discuss the increasing evidence that consumption of green tea has preventative effects in obesity, hypertension, insulin resistance, type II diabetes, atherosclerosis, coronary heart disease and Metabolic Syndrome (MetS). The catechins in green tea has been found to be beneficial in obesity induced by a high-fat diet. These effects are mainly attributable to the gallat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Tea is one of the favorite beverages consumed worldwide ( 11 ). Vast accumulative evidence suggests that the consumption of tea and its components have various potential health benefits ( 12 ), including the prevention of cardiovascular diseases and cancer and its antibacterial, antiangiogenic, antiarthritic, anti-inflammatory, antioxidative, cholesterol-lowering, neuroprotective, and antiviral effects ( 13 ). Previous studies have indicated that tea consumption is correlated with a lower risk of stroke, depressive symptoms, and cognitive impairment ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tea is one of the favorite beverages consumed worldwide ( 11 ). Vast accumulative evidence suggests that the consumption of tea and its components have various potential health benefits ( 12 ), including the prevention of cardiovascular diseases and cancer and its antibacterial, antiangiogenic, antiarthritic, anti-inflammatory, antioxidative, cholesterol-lowering, neuroprotective, and antiviral effects ( 13 ). Previous studies have indicated that tea consumption is correlated with a lower risk of stroke, depressive symptoms, and cognitive impairment ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous extract of sour tea has the greatest antioxidant activity of all the components. The existence of an adequate supply of mucilage with soluble dietary fibers in the sepals of sour tea is one of its additional properties, it should be emphasized [12]. Within 22-35 days after blooming, there is a rise in mucilage of roughly 15-28%, which results in sour tea.…”
mentioning
confidence: 99%